2019
DOI: 10.1021/acs.jpcb.8b10271
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Fluorescence Enhancement of Benzaldehydes by Intermolecular Hydrogen Bonding

Abstract: Density functional theory and its time-dependent extension are employed to investigate the intermolecular hydrogen-bonding- (Inter-HB-) induced fluorescence enhancement of benzaldehydes. The fluorescence quenching mechanism of benzaldehydes in chloroform is attributed to the low energy gap between the lowest ππ* and nπ* states at Franck–Condon (FC) point and conical interaction between ππ* and nπ* states. The Inter-HB between the aldehyde group of benzaldehydes and methanol can considerably increase the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 38 publications
2
33
1
Order By: Relevance
“…9−12 Second, our recent theoretical study has demonstrated that TDDFT may underestimate the coupling between the ππ* and nπ* states and could not accurately predict the CI between the two states. 23 As reported in Table 1, the XMCQDPT2 computed vertical excitation energies (VEEs) of the six fluorescein derivatives in water were essentially identical and approximately 3.08 eV, which was larger than the experimentally measured absorption maxima (AM) of fluorescein in acidic media (437 nm, 2.84 eV), i.e., approximately 0.24 eV. 29 Due to neglecting the vibronic couplings and relaxation effects, the computed VEEs did not exactly correspond to the experimentally measured AM and were typically larger than AM by ca.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…9−12 Second, our recent theoretical study has demonstrated that TDDFT may underestimate the coupling between the ππ* and nπ* states and could not accurately predict the CI between the two states. 23 As reported in Table 1, the XMCQDPT2 computed vertical excitation energies (VEEs) of the six fluorescein derivatives in water were essentially identical and approximately 3.08 eV, which was larger than the experimentally measured absorption maxima (AM) of fluorescein in acidic media (437 nm, 2.84 eV), i.e., approximately 0.24 eV. 29 Due to neglecting the vibronic couplings and relaxation effects, the computed VEEs did not exactly correspond to the experimentally measured AM and were typically larger than AM by ca.…”
mentioning
confidence: 99%
“…The energy of the nπ* state was larger than that of the ππ* state by only approximately 0.26 eV (see Figure b and Table ). The vibronic interaction between the close-lying ππ* and nπ* states can cause a significant fluorescence quenching of aromatic carbonyl compounds, and two different mechanisms can explain this phenomenon. The first one is the so-called “proximity effect” which states that the nonradiative decay rate of the ππ* state will increase due to the vibronic coupling between the ππ* and nπ* states along the out-of-plane bending modes . The second one was proposed by us recently .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 Generally, the H-bond network facilitates internal conversion (IC) processes; 4,5 however, in some cases fluorescence enhancement is observed. 6,7 In the past decade, several studies reported nonconventional absorption due to charge transfer transitions 8 and anomalous photoluminescence induced by molecular aggregation or confinement of many common organic moieties. 9,10 Similarly, an anomalous fluorescence emission was observed in aqueous solutions of many peptides, proteins, and amyloid aggregates in the absence of any aromatic residue or π system.…”
mentioning
confidence: 99%